Development of a Detailed Chemical Kinetic Model for 1-Methylnaphthalene - Junjie Liang; Qianlong Zhang; Yijun Heng; Gesheng Li; Ke Yang; Ruiyang Wang; Fan Dong; Neng Zhu (Molecules)
1-Methylnaphthalene is a critical component for constructing fuel surrogates of diesel and aviation kerosene. However, the reaction pathways of 1-methylnaphthalene included in existing detailed chemical kinetic models vary from each other, leading to discrepancies in the simulation of ignition and oxidation processes. In the present study, reaction classes and pathways involved in the combustion of 1-methylnaphthalene were analyzed, and effects of rate constants of reactions related to 1-methylnaphthalene and its significant intermediates on ignition delay times and species concentration profiles were discussed, involving hydrogen abstraction and substitution reactions of 1-methylnaphthalene, oxidation, isomerization, and addition reactions of 1-naphthylmethyl, hydrogen abstraction and oxidation reactions of indene, as well as the oxidation of indenyl and naphthalene. On this basis, a new detailed chemical kinetic model for 1-methylnaphthalene was developed, which includes 1389 species and 7185 reactions. The validation of this mechanism shows that it can predict accurately the available experimental ignition delay times, species concentration profiles, and laminar flame speeds of 1-methylnaphthalene. Finally, reaction paths and sensitivity analysis of ignition delay times were performed using the proposed reaction mechanism, and the result shows that the conversion of 1-methylnaphthalene to 1-naphthaldehyde plays an important role in its ignition.